The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/polym12030668
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Waterborne UV Lacquer Product Modified by Zinc Oxide with Flower Shape

Abstract: In this paper, the waterborne UV lacquer product (WUV) was used as the main raw material, zinc oxide (ZnO) was used as the additive, and the stearic acid as the surface modifier. According to the method of spraying coating on the surface of poplar wood (Populus tomentosa), a simple and efficient preparation method was carried out to generate a super-hydrophobic surface and enhance the erosion resistance of the coating. By testing, the contact angle (CA) of water on the coating surface can reach 158.4°. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Nanoparticles of metal oxides and silica as wood coating additives allow the preparation of surfaces with a wide array of functionalities. An interesting method to achieve superhydrophobicity was to modify the nanoparticles with a low surface free energy chemical before their incorporation into the coating [85][86][87][88]. The low surface free energy of both the modified nanoparticles and the resin would imbue water repellency, and the nanoparticles brought an appropriate micro-/nanoscale architecture to the coating, joining together the two requirements to achieve superhydrophobicity.…”
Section: Additives In Organic Coatingsmentioning
confidence: 99%
“…Nanoparticles of metal oxides and silica as wood coating additives allow the preparation of surfaces with a wide array of functionalities. An interesting method to achieve superhydrophobicity was to modify the nanoparticles with a low surface free energy chemical before their incorporation into the coating [85][86][87][88]. The low surface free energy of both the modified nanoparticles and the resin would imbue water repellency, and the nanoparticles brought an appropriate micro-/nanoscale architecture to the coating, joining together the two requirements to achieve superhydrophobicity.…”
Section: Additives In Organic Coatingsmentioning
confidence: 99%
“…This physical method can be applied through dipping, brushing and spraying [ 150 ]. Wu et al [ 151 ] reported that a superhydrophobic coating was constructed on the surface of poplar wood with a contact angle of up to 158.4° through the waterborne UV lacquer product (WUV) which was modified by ZnO nanoparticles and stearic acid. Compared with WUV, the water resistance of zinc stearate/waterborne UV lacquer super-hydrophobic coating (ZnSt 2 /WUV) was stronger, which was conducive to prepare superhydrophobic coatings in an easy and environmentally friendly.…”
Section: Applicationsmentioning
confidence: 99%
“…Low glossiness is required for infrared and visible light-compatible coatings. As a new infrared low-emissivity resin, UV-curable coating has the advantages of high curing rate [7], but has the disadvantages of low adhesion and high glossiness [8], which limits its application in infrared low-emissivity materials and is not conducive to infrared light and visible light compatibility [9]. The widely used UV coating system in the industry is unsaturated urethane acrylate [10], and the UV-curable light wavelength is the irradiation wavelength of a medium pressure mercury lamp (310-1000 nm) [11].…”
Section: Introductionmentioning
confidence: 99%